การเมืองเรื่องการเลือกตั้งระดับชาติและระดับท้องถิ่นในเทศบาลเมืองหลังสวน - จุฑารัตน์ ลิมปกาญจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this dissertation is to qualitatively assess 1) the key factors that affect Langsuan Municipality population’s voting decision during National elections and Local elections, and 2) the Democrat Party’s role in Local elections. This study is undergone through documentary research in relation to relevant theory and depth interview. The study sample was composed of 62 voters who live in Langsuan Municipality. The results show that political Party, characteristics of the candidates, and Policy platform respectively are the most important factors affecting voting decision at the National elections, while characteristics of the candidate, Policy platform, and Campaign Strategy respectively are the most important factors affecting voting decisions at the Local elections. Findings also reveal that the Democrat Party’s role during Local elections is limited because the majority of population do not take National level political party into consideration during Local elections. Analyzing the role of Democrat Party members in Chumphon Province reveal that each party member play important roles in building and reaching the core voters for the Democrat Party.